Evaluating a voriconazole dose modification guideline to optimize dosing in patients with hematologic malignancies. (September 2019) - Perreault, Sarah; McManus, Dayna; Anderson, Anthony; Lin, Tiffany; Ruggero, Michael; Topal, Jeffrey E
Background: Voriconazole is an azole antifungal utilized for prophylaxis and treatment of invasive fungal infections in hematologic patients. Previous studies have revealed decreased efficacy and increased toxicity with subtherapeutic <1 mcg/mL and supratherapeutic > 4 mcg/mL levels. A voriconazole dose modification guideline was introduced in July 2014 based on a retrospective analysis. Objective: The primary objective was to evaluate the voriconazole dose modification guideline. Secondary objectives were to identify patient-specific characteristics that contribute to inadequate levels, adverse effects, and breakthrough invasive fungal infections. Methods: This prospective study included 128 patients with 250 admissions who received voriconazole from July 2014 to February 2016. Eligible adult patients receiving voriconazole for prophylaxis or treatment with at least one trough level, drawn appropriately, were included. Demographics, adverse effects, and breakthrough invasive fungal infections were documented. Results: Voriconazole use was categorized as: new start, new start with loading dose, or continuation of home therapy. The median initial levels were 1.5, 3.5, and 1.7 mcg/mL with 62% (73/119), 55% (6/11), and 60% (72/120) within the therapeutic range, respectively. Using the voriconazole dose modification guideline, 80% were within goal by the second dose adjustment. Age ≤ 30 and BMI ≤ 25 kg/m 2 had higher rates of subtherapeutic levels in the new start cohorts ( p  = 0.024 and p  = 0.009). Approximately 7.6% of patients experienced an adverse effect with neurologic/psychological being the most common. A total of 8.5% of patients had a possible, probable or proven breakthrough invasive fungal infections while on voriconazole. Conclusion: Using the voriconazole dose modification guideline, the number of patients that reached therapeutic range improved from 36% to 80% by the second dose adjustment ( p  = 0.007). This voriconazole dose modification guideline can be utilized to help dose and adjust voriconazole in order to achieve therapeutic levels.